2010
DOI: 10.1177/102490791001700204
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Clinical Trial Comparing Self‐Administered Nitrous Oxide and Haematoma Block for Analgesia in Reducing Fracture of the Distal Radius in an Emergency Department

et al.

Abstract: To compare the effectiveness and efficacy of self-administered nitrous oxide and haematoma block in pain relief during close reduction of fractured distal radius in adult patients. Methods: This was a prospective clinical trial. All adult patients aged 18 years or above with fracture of the distal radius within 24 hours requiring close reduction in the Accident and Emergency Department of Kwong Wah Hospital were included. Patients with known contraindications were excluded. A consecutive series of patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A pilot study by Orbach et al with a hematoma block reported a mean VAS score of 5.50 in one group (10 mL of 2% lidocaine) and 3.09 in another group (20 mL of 1% lidocaine) although the difference was not statistically significant [ 6 ]. Another study revealed an average VAS score of 7.19 for the Entonox group and 2.8 for the hematoma block group [ 9 ]. A study comparing hematoma block and brachial plexus block reported a mean VAS score of 2.08 for the hematoma block and 1.60 for the brachial plexus block [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pilot study by Orbach et al with a hematoma block reported a mean VAS score of 5.50 in one group (10 mL of 2% lidocaine) and 3.09 in another group (20 mL of 1% lidocaine) although the difference was not statistically significant [ 6 ]. Another study revealed an average VAS score of 7.19 for the Entonox group and 2.8 for the hematoma block group [ 9 ]. A study comparing hematoma block and brachial plexus block reported a mean VAS score of 2.08 for the hematoma block and 1.60 for the brachial plexus block [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a wide variety of pain perception during fracture manipulation under hematoma block, with patients reporting highly varied mean visual analog scale (VAS) scores: 5.50 [ 6 ], 2.8 [ 9 ], 2.08 [ 5 ], and 0.97 [ 4 ]. Tageldin’s periosteal block reported a VAS score of 0 in 36 patients and a VAS score between 1-3 in six patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both the techniques have been studied independently and also compared with other techniques such as sedation, brachial plexus block, etc. [8][9][10] However, there is no study in the literature till date which has combined these two techniques. HB and IVRA together are also an attractive option since they do not require expertise or equipments such as ultrasound or peripheral nerve stimulator needed for brachial plexus block and hazards of GA are obviated.…”
Section: Introductionmentioning
confidence: 99%